Beyond constructs and principles: addressing gender-related barriers to high, equitable immunization coverage - Gerber, Willow; Fields, Rebecca; Guesela, Neide; Nuhu, Khadijah A. Ibrahim; Manika, Eugene (Frontiers in Global Women's Health, 2024)
The global immunization community has only recently recognized that addressing gender-related barriers to vaccination is critical to improving equity and increasing protection against vaccinepreventable diseases. USAID's MOMENTUM Routine Immunization Transformation and Equity project aims to strengthen routine immunization programs to overcome entrenched obstacles to reaching zero-dose and under-immunized children while supporting the introduction of other new vaccines given over the life course. From the outset, the project recognized the need to mainstream gender into its global and country level work, incorporating gender considerations into all phases of the program cycle, from assessment to activity design, strategic communications, monitoring, evaluation, and continuous learning. Its gender mainstreaming efforts focus on five areas of improvement for immunization: service access and convenience; service quality and experience; communication and demand generation for immunization among caregivers (both women and men) and families; making services more responsive to agency and autonomy constraints of female caregivers; and the conditions and circumstances of health workers, who are mostly women. The